Tapal Kuda Bergolak: Suatu Kajian tentang Resistensi terhadap Pelengseran Presiden Gus Dur 2001 - Abd. Latief Bustami (Antropologi Indonesia, 2011)
This article describes social resistance in Tapal Kuda community against The People Consultative Assembly (Majelis Permusyawaratan Rakyat) who deposed President Wahid (Gus Dur) in 2001. Their resistance resulted in loss of human life as well as the destruction of religious buildings, educational institutions, and other public facilities, which are believed to have historical connections to their opponents, i.e. Muhammadiyah or its leader, Amien Rais. The Tapal Kuda community shares typical cultural characteristics such as Maduranese, Muslim, “remain traditional”, based on Ulama, and made their kiai (religious leader) as the highest role-model. Additionally, they have developed network of religious boarding schools of Tarekat Naqsyabandiah wal Qadiriah and classifying them into hierarchy of “core schools” (pesantren induk) and their sub-levels.The resistance shows symbolic manipulations made up by local elite leaders for fabricating profane symbols into a sacred ones in a way that unmistakebly drawing political dimension into intra-religious conflicts. The tension appeared in how they define themselves as minna (saya, as self) and minkum (kamu, the others). This definition had became a moral basis that justified their act in destroying the opponents as the others. It is important to see how value of Islamic solidarity within traditional muslim community in Madura tends to get firmer while paradoxically the wholeness of Muslim brotherhood is under threat. Key words: Tapal Kuda, Madura, kiai, pesantren, resistance, Nahdlatul Ulama, Muhammadiyah